Crystal engineering: an outlook for the future - Nangia, Ashwini K.; Desiraju, Gautam R. (Angewandte Chemie-International Edition, 2019)
Crystal Engineering has traditionally dealt with molecular crystals. It is the understanding of intermolecular interactions in the context of crystal packing and in the utilization of such understanding in the design of new solids with desired physical and chemical properties. We outline here five areas which come under the umbrella of Crystal Engineering and where we feel that a proper planning of research efforts could lead to higher dividends for science together with greater returns for humankind. We touch on themes and domains where science funding and translation efforts could be directed in the current climate of a society that increasingly expects applications and utility products from science and technology. The five topics are: 1)pharmaceutical solids; 2)industrial solid state reactions; 3)mechanical properties with practical applications; 4)MOFs and COFs framework solids; 5)new materials for solar energy harvesting and advanced polymers.
Keywords: crystal engineering; metal-organic frameworks; pharmaceutical solids; solar energy; solid-state reactions